1996
DOI: 10.1111/j.1365-2052.1996.tb01175.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of 45 polymorphic microsatellites from the bovine genome

Abstract: Summary A small‐insert bovine genomic library was constructed in pBluescript II SK(+) and enriched for microsatellites by selective rescue of single‐stranded pBluescript DNA carrying (CA)n/(TG) n tandem repeats. Approximately 50% of the clones in the enriched library contained (CA) nrepeats or CA‐rich sequences. Sequencing of clones selected for (CA) n repeats resulted in the identification and characterization of 45 (CA) npolymorphic microsatellites. Genotyping in 9 large paternal half‐sib families indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The results in Figures 3 and 4 revealed that the microsatellite within the 5′-flanking region of the bovine GHSR1a gene was transcribed as the 5′-UTR of a non-spliced transcript, GHSR1b, and expression level of the mRNA of GHSR1b was more than threefold higher than that of GHSR1a. Furthermore, the present results confirm earlier reports by Ma et al (1996) that microsatellite ((TG)n) locus is very highly polymorphic (17 alleles: TG-repeat numbers: 10 to 33; Table 1). It has been reported that the length of the TG-repeat in the P1 promoter region of the growth hormone receptor (GHR) gene is significantly related to growth and carcass traits in beef cattle (Hale et al 2000;Curi et al 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The results in Figures 3 and 4 revealed that the microsatellite within the 5′-flanking region of the bovine GHSR1a gene was transcribed as the 5′-UTR of a non-spliced transcript, GHSR1b, and expression level of the mRNA of GHSR1b was more than threefold higher than that of GHSR1a. Furthermore, the present results confirm earlier reports by Ma et al (1996) that microsatellite ((TG)n) locus is very highly polymorphic (17 alleles: TG-repeat numbers: 10 to 33; Table 1). It has been reported that the length of the TG-repeat in the P1 promoter region of the growth hormone receptor (GHR) gene is significantly related to growth and carcass traits in beef cattle (Hale et al 2000;Curi et al 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The use of minisatellites in DNA fingerprinting and identification of individuals was first described in humans [ 11 , 12 ], rapidly also entering the area of domestic animal identification and pedigree analysis [ 13 ]. Initial steps in using mini- and microsatellites in cattle identification and parentage control were done only a few years later [ 14 , 15 ] and further actions were taken to establish a robust and internationally comparable panel of markers [ 16 20 ]. In international comparison tests under the direction of the International Society for Animal Genetics (ISAG) a panel of at least 12 microsatellite markers (short tandem repeats-STR) was established for parentage control in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Although their construction requires large amounts of high molecular weight DNA, numerous libraries were constructed successfully from partially digested chromosomal DNA by cloning into cosmid (Stallings et al 1990; Nizetic et al 1994; Ma et al 1996), fosmid (Kim et al 1995; Gingrich et al 1996), yeast artificial chromosome (YAC) (McCormick et al 1993a, b), and, later, bacterial artificial chromosome (BAC) (Šafář et al 2004; Janda et al 2006) vectors. As the sorting of millions of chromosomes needed to construct libraries cloned in YAC and BAC vectors is a daunting task, an alternative approach has been used and genomic YAC or BAC library is constructed and screened with a probe prepared either from a chromosome-specific cosmid library (Kim et al 1994) or from DNA from flow-sorted chromosomes (Sankovic et al 2006) to identify clones coming from the chromosome of interest and assemble a chromosome-specific sub-library.…”
Section: The Many Important Uses Of Flow-sorted Chromosomesmentioning
confidence: 99%